Introduction to the special issue on foreign language anxiety: Theoretical and methodological developments - Botes, Elouise; Dewaele, Jean-Marc; Greiff, Samuel (Studies in Second Language Learning and Teaching, 2025)
This introduction outlines the theoretical and methodological developments that have shaped research on foreign language anxiety since Scovel’s (1978) foundational review. Building on MacIntyre’s (2017) synthesis of the confounding, specialized, and dynamic phases, we argue that the field has entered a new contextual phase characterized by increasingly narrow, context-specific research questions and more sophisticated analytic approaches. We summarize eight contributions included in this special issue, which collectively span person-centered, cross-cultural, physiological, dynamic, and task-specific examinations of language anxiety. These studies expand the nomological network of language anxiety by incorporating constructs such as shame, guilt, and imposter phenomenon; revisit debates surrounding the directionality of the anxiety-proficiency relationship; and employ innovative methodologies including latent profile analysis, Bayesian modelling, heart-rate variability, and experience sampling. Together, they demonstrate how language anxiety is best understood as a contextually grounded and dynamic construct.